SPOKOJNY SEN KLITAJMESTRY ALBO CZEGO „BRAK” W EURYPIDESOWEJ „ELEKTRZE" - Komorowska, Joanna (Colloquia Litteraria, 2009)
Peaceful dream of Clytemnestra, or what is missing in Euripides’ Electra Clytemnestra’s dream features as an important element of the vengeance dramas of both Aeschylus and Sophocles: still, is remains absent from the Euripidean version. This short essay sketches the possible implications of such an ‘omission’, while simultaneously highlighting the highly contrasting implications of the dream in the Choephorae and in the Sophoclean Electra.